FAKTOR-FAKTOR YANG MEMPENG ARUHI PERHITUNGAN ANGGARAN PENDAPATAN DAN BELANJA NEGARA - I .H, Maulidiyah.; Wahyudi, M. (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2001)
The role of government on development is really needed; APBN (budget income of state) is one of fiscal policy to create the aim of development. The arrangement of APBN needs to concern the influence factors, namely a rate of exchange rupiah to US dollar, economic development, and fuel price in world market, national inflation level, and crude oil production per day. To find out the influence of each variable, it needs to regress the existent variable, after that to find out validity of the influence is by examining statistic criteria and estimating the deviation of classic assumption. The result of the estimation does not show any serious deviation classic assumption that is able to hamper the estimation, and from the result examination it finds out that the statistic criteria does not has problem.